Relationship of Some Anthropometric Measurements With The Explosive Strength of the Upper and Lower Extremities with the Rhythmic Gymnastics of Female Students - Hala Razzaq Mudalloul (Indian Journal of Forensic Medicine & Toxicology, 2020)
Identify the relationship between some anthropometric measurements and the explosive power of the upperand lower extremities of female students in rhythmic gymnastics. The research sample consisted of studentsfrom the University of Kufa / College of Physical Education and Sports Science where the research sampleunderwent field tests to measure the explosive power of the upper and lower extremities and after conductingstatistical treatments and presenting the results and analyzing and discussing the researcher reached To a setof conclusions, including there is an inverse correlation between age and the explosive force of the upperand lower extremities, and there is a direct correlation between body length and the explosive force of theupper and lower extremities.